1984
DOI: 10.1128/aem.48.5.975-979.1984
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Electrophoretic Assessment of the Genetic Structure and Diversity of Yersinia ruckeri

Abstract: Multilocus isoenzyme electrophoresis was used to screen 47 field isolates of Yersinia ruckeri for electrophoretic variation at 15 enzyme loci. Only four electrophoretic types were observed, thus indicating that the genetic structure of Y. ruckeri is clonal. Forty-two isolates were of one electrophoretic type, a reflection of the low amount of genetic diversity extant in this species. Although sorbitol fermentation has been considered to be indicative of a second biotype, no significant gene frequency differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…On the other hand, although on the basis of results obtained in multilocus isoenzyme analysis (Schill et al 1984) and dot-blot hybridization experiments (De Grandis et al 1988), it has been reported that the genetic intraspeci®c diversity in Y. ruckeri is low, some variability was detected when pulsed-®eld gel electrophoresis was employed (Romalde, Iteman & Carniel 1991). The results obtained in this study in the ribotyping analysis of the Portuguese isolates, with six or seven ribopatterns being detected with any of the endonucleases employed, clearly support this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, although on the basis of results obtained in multilocus isoenzyme analysis (Schill et al 1984) and dot-blot hybridization experiments (De Grandis et al 1988), it has been reported that the genetic intraspeci®c diversity in Y. ruckeri is low, some variability was detected when pulsed-®eld gel electrophoresis was employed (Romalde, Iteman & Carniel 1991). The results obtained in this study in the ribotyping analysis of the Portuguese isolates, with six or seven ribopatterns being detected with any of the endonucleases employed, clearly support this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great serological variability within Y. ruckeri, with several intraspecies classi®cations being proposed, comprising four (Romalde, Magarin Äos, Barja & Toranzo 1993) or ®ve (Davies 1990) different O-serotypes. On the other hand, genetic intraspeci®c diversity in this bacterial species is very low as demonstrated by Schill, Phelps & Pyle (1984), using multilocus isoenzyme analysis, by De Grandis, Krell, Flett & Stevenson (1988), employing dot blot hybridization assays on nitrocellulose ®lters, and by Romalde et al (1993), by means of restriction fragment length polymorphism studies.…”
Section: Introductionmentioning
confidence: 99%
“…salmonicida according to their geographic origin than multilocus enzyme electrophoresis [13] and ribotyping [10]. These methods were applicable for the species with a low genotypic diver- sity, as in the case of Yersinia ruckeri [14,15]. On the other hand, Ha «nninen and Hirvela «-Koski [16] concluded that ribotyping would provide better results than PFGE for epidemiological studies of A. salmonicida ssp.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that strains biochemically identified as Y. frederiksenii represented more than one Yersinia species [8]. Schill et al [9] used MLEE to assess genetic diversity of Y. ruckeri, which causes enteric red mouth disease, a serious infectious disease in the rainbow trout farming industry that causes economic losses in many countries. Y. ruckeri was fairly clonal as the strains were found to belong primarily to one electrophoretic type.…”
Section: Multilocus Enzyme Electrophoresismentioning
confidence: 99%